Response of bio-fertilizers, levels of nitrogen and different row spacings on productivity of chickpea (Cicer arietinum L.) - KUMAR, RAJ; Kumar, MUNISH; KUMAR, DURGESH; VERMA, RAMESH (Journal of Soil and Water Conservation, 2024)
An experiment was conducted at Kanpur, during rabi 2014-15 and 2015-16 to find out the response of row spacing, bio-fertilizer, and nitrogen levels on yield and yield attributes of chickpeas. The treatments comprised of row spacing i.e. 40 cm and 60 cm, biofertilizer i.e. Rhizobium leguminosarum culture (seed coating @ 20 g kg-1 seed), Phosphate solubilizing bacteria (PSB) @ 2.5 kg ha-1 in soil and Rhizobium leguminosarum + Phosphate solubilizing bacteria (PSB) and nitrogen level i.e. 10, 20 and N30 kg ha-1 in Split plot design with 3 replications. The results showed that 60 cm row spacing produced significantly higher yield attributes in both years on pooled basis-number of pods plant-1 (57.57), a number of seeds pod-1 (1.72), 1000-seed weight (147.64 g), nodules plant-1 at 50 DAS (28.08), fresh & dry weight nodules plant-1 at 50 DAS (76.58 and 44.37 mg) and protein content (21.06%). Among the bio-fertilizers, the performance of dual inoculation of Rhizobium leguminosarum culture + PSB was recorded as significantly superior with regard to the number of pods plant-1 (57.61), number of seeds pod-1 (1.89), 1000- seed weight (148.75) nodules plant-1 at 50 DAS (29.70), fresh & dry weight nodules plant-1 at 50 DAS (81.34 and 48.12 mg) and protein content (21.26%). Nitrogen level @ 30 kg ha-1 recorded significantly higher No. of pod plant-1 (147.64 g), number of seeds pod-1 (1.97), 1000- seed weight (149.47g), nodules plant-1 at 50 DAS (30.54), fresh & dry weight nodules/plant at 50 DAS (81.34 and 48.12 mg) and protein content (21.15%). The 40 cm row spacing produced significantly higher yield in both years on the pool basis - seed yield recorded (14.22 q ha-1), stover yield (20.20 q ha-1), harvest index (41.16%), gross return Rs. 75593 ha-1, net return Rs. 56972 ha-1 and B.C. ratio 1:3.07. Among the biofertilizers, the performance of dual inoculation of Rhizobium leguminosarum + PSB was recorded as significantly superior with seed yield (14.33 q ha-1), stover yield (19.15 q ha-1), harvest index (42.48%), gross return Rs. 76047 ha-1, net return Rs. 58225 ha-1 and B:C ratio 1:3.27. However, nitrogen level @ 30 kg ha-1 recorded significantly higher on seed yield (14.83 q ha-1), stover yield (19.97 q ha-1), harvest index (42.83%), gross return Rs. 78728 ha-1, net return Rs. 60994 ha-1 and B:C ratio1:3.44.